Universal Accessibility to Cultural Heritage in Spain: A Bibliometric Review - Antonio del Bosque; Pablo Fernández-Arias; Patricia Castro-López; María Nieto-Sobrino; Diego Vergara (Buildings)
Universal accessibility in cultural heritage is a key challenge to ensure the inclusion of all visitors in historical and tourist environments. The aim of this research is to analyze the current state of research on universal accessibility to cultural heritage in Spain, identifying the key institutions, themes, and trends within this field. Additionally, it seeks to assess how these findings relate to national priorities and highlight gaps in the implementation of accessibility measures. This study employed the PRISMA 2020 framework to select and analyze 1035 scientific articles published between 2010 and 2025, retrieved from the Scopus and Web of Science databases. Bibliometrix (an R package) and Biblioshiny were used to analyze the data. The results show an exponential growth in publications since 2018, highlighting key areas such as accessible tourism, digitalization, the use of technologies for heritage documentation, urban planning, and geo-heritage conservation. It is concluded that accessibility in cultural heritage is an expanding interdisciplinary field with increasing international significance. It is recommended to continue exploring innovative technological solutions, strengthen governance strategies, and expand studies to rural and natural environments to ensure truly universal accessibility.